Role of STAT3 in skin fibrosis and transforming growth factor beta signalling. (23rd September 2017) - Pedroza, Mesias; To, Sarah; Assassi, Shervin; Wu, Minghua; Tweardy, David; Agarwal, Sandeep K
Abstract: Objective: SSc is an autoimmune disease characterized by progressive fibrosis of the skin and internal organs. IL-6 and related cytokines that signal through STAT3 have been implicated in the pathogenesis of SSc and mouse models of fibrosis. The aim of this study was to investigate the efficacy of inhibiting STAT3 in the development of fibrosis in two mouse models of skin fibrosis. Methods: Biopsy samples of skin from SSc patients and healthy control subjects were used to determine the expression pattern of phosphotyrosyl (pY705)-STAT3. C188-9, a small molecule inhibitor of STAT3, was used to treat fibrosis in the bleomycin-induced fibrosis model and Tsk-1 mice. In vitro studies were performed to determine the extent to which STAT3 regulates the fibrotic phenotype of dermal fibroblasts. Results: Increased STAT3 and pY705-STAT3 was observed in SSc skin biopsies and in both mouse models of SSc. STAT3 inhibition with C188-9 resulted in attenuated skin fibrosis, myofibroblast accumulation, pro-fibrotic gene expression and collagen deposition in both mouse models of skin fibrosis. C188-9 decreased in vitro dermal fibroblast production of fibrotic genes induced by IL-6 trans-signalling and TGF-β. Finally, TGF-β induced phosphotyrosylation of STAT3 in a SMAD3-dependent manner. Conclusion: STAT3 inhibition decreases dermal fibrosis in two models of SSc. STAT3 regulates dermal fibroblasts function in vitro and can be activated by TGF-β. These data suggest that STAT3 is a potential therapeutic target for dermal fibrosis in diseases such as SSc.